2018
DOI: 10.13057/biodiv/d190122
|View full text |Cite
|
Sign up to set email alerts
|

Nest existences and population of Pangolin (Manis javanica Desmarest, 1822) at the designated area of Cisokan Hydropower, West Java, Indonesia

Abstract: Withaningsih S, Noorahya F, Megantara EN, Parikesit, Husodo T. 2018. Nest existences and population of Pangolin (Manis javanica Desmarest, 1822) at the designated area of Cisokan Hydropower, West Java, Indonesia. Biodiversitas 19: 153-162. Pangolin (Manis javanica) is one of the unique mammals found in Indonesia, which is categoryzed as protected species. However, the scientific information regarding with the population and distribution of this species is still low. Therefore, the study aimed to estimate the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Insectivores (16%) (Andreychev 2020) are somewhat inferior to rodents. In comparison to Cisokan, Cianjur, West Java, Indonesia, the proportion of rodent species from other mammals is higher (Withaningsih et al 2018;Husodo et al 2019). This is a feature differing Mordovia of many other mammal faunas, where representatives of the other animal orders predominate (Wirdateti et al 2013;Sulistyadi 2016;Medina et al 2018;Shanidah et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Insectivores (16%) (Andreychev 2020) are somewhat inferior to rodents. In comparison to Cisokan, Cianjur, West Java, Indonesia, the proportion of rodent species from other mammals is higher (Withaningsih et al 2018;Husodo et al 2019). This is a feature differing Mordovia of many other mammal faunas, where representatives of the other animal orders predominate (Wirdateti et al 2013;Sulistyadi 2016;Medina et al 2018;Shanidah et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This is a high indicator among other units. In comparison for Cisakan, Cianjur, West Java, Indonesia, the proportion of insectivorous species from other mammals is 7.7% (Withaningsih et al 2018;Husodo et al 2019). This is a distinctive feature of Mordovia from many mammalian faunas, where representatives of the orders carnivores, rodents and bats predominate (Wirdateti et al 2013;Sulistyadi 2016;Medina et al 2018;Shanidah et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Several research articles revealed that in Cisokan, the Pangolin was estimated at 6-20 individuals. The estimation was undertaken based on the analysis of location, time, and individual morphology (Withaningsih et al 2018). Leopard cat was estimated at 7-12 individuals, without information about gender .…”
Section: Mammalian Diversitymentioning
confidence: 99%